A prospective cohort study on active surveillance after neoadjuvant chemoradiotherapy for esophageal cancer: protocol of Surgery As Needed for Oesophageal cancer-2 - Charlène J. van der Zijden; Sjoerd M. Lagarde; Merel Hermus; Leonieke W. Kranenburg; J. Jan B. van Lanschot; Bianca Mostert; Joost J. M. E. Nuyttens; Lindsey Oudijk; Pieter C. van der Sluis; Manon C. W. Spaander; Maria J. Valkema; Roelf Valkema; et al. (BMC Cancer, 2023)
Abstract Background Neoadjuvant chemoradiotherapy (nCRT) followed by esophagectomy is a standard treatment for potentially curable esophageal cancer. Active surveillance in patients with a clinically complete response (cCR) 12 weeks after nCRT is regarded as possible alternative to standard surgery. The aim of this study is to monitor the safety, adherence and effectiveness of active surveillance in patients outside a randomized trial. Methods This nationwide prospective cohort study aims to accrue operable patients with non-metastatic histologically proven adenocarcinoma or squamous cell carcinoma of the esophagus or esophagogastric junction. Patients receive nCRT and response evaluation consists of upper endoscopy with bite-on-bite biopsies, endoscopic ultrasonography plus fine-needle aspiration of suspicious lymph nodes and 18F-fluorodeoxyglucose positron emission tomography/computed tomography scan. When residue or regrowth of tumor in the absence of distant metastases is detected, surgical resection is advised. Patients with cCR after nCRT are suitable to undergo active surveillance. Patients can consult an independent physician or psychologist to support decision-making. Primary endpoint is the number and severity of adverse events in patients with cCR undergoing active surveillance, defined as complications from response evaluations, delayed surgery and the development of distant metastases. Secondary endpoints include timing and quality of diagnostic modalities, overall survival, progression-free survival, fear of cancer recurrence and decisional regret. Discussion Active surveillance after nCRT may be an alternative to standard surgery in patients with esophageal cancer. Similar to organ-sparing approaches applied in other cancer types, the safety and efficacy of active surveillance needs monitoring before data from randomized trials are available. Trial registration The SANO-2 study has been registered at ClinicalTrials.gov as NCT04886635 (May 14, 2021) – Retrospectively registered.